2019
DOI: 10.1371/journal.pone.0209310
|View full text |Cite
|
Sign up to set email alerts
|

Illusory face detection in pure noise images: The role of interindividual variability in fMRI activation patterns

Abstract: Illusory face detection tasks can be used to study the neural correlates of top-down influences on face perception. In a typical functional magnetic resonance imaging (fMRI) study design, subjects are presented with pure noise images, but are told that half of the stimuli contain a face. The illusory face perception network is assessed by comparing blood oxygenation level dependent (BOLD) responses to images in which a face has been detected against BOLD activity related to images in which no face has been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Because pareidolia is a subjective experience influenced by top-down factors, we hypothesized that there should be individual variability in the frequency of these percepts. In line with this, we found that pareidolia experiences are reported with varying prevalence across studies that have used the same or similar experimental design (Liu et al, 2014 ; Rieth, Lee, Lui, Tian, & Huber, 2011 ; Zhang et al, 2008 ; Zimmermann, Stratil, Thome, Sommer, & Jansen, 2019 ). In Zhang et al ( 2008 ), the percentage of face-present responses in 16 subjects ranged from nearly 8% to more than 50% (standard deviation (SD) = 14%).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Because pareidolia is a subjective experience influenced by top-down factors, we hypothesized that there should be individual variability in the frequency of these percepts. In line with this, we found that pareidolia experiences are reported with varying prevalence across studies that have used the same or similar experimental design (Liu et al, 2014 ; Rieth, Lee, Lui, Tian, & Huber, 2011 ; Zhang et al, 2008 ; Zimmermann, Stratil, Thome, Sommer, & Jansen, 2019 ). In Zhang et al ( 2008 ), the percentage of face-present responses in 16 subjects ranged from nearly 8% to more than 50% (standard deviation (SD) = 14%).…”
Section: Introductionsupporting
confidence: 70%
“…Previous studies of face pareidolia in noise have focused on the paradigm of Exp. 1a (Li et al, 2009(Li et al, , 2010Liu et al, 2014;Rieth et al, 2011;Zhang et al, 2008;Zimmermann et al, 2019), but our additional experiments demonstrate that this paradigm can be adapted to reveal the various factors that contribute to pareidolia proneness.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…High interindividual variability of the hemispheric lateralization of the face peerception network is also in accordance with our own anecdotal experience. Our research group has conducted numerous fMRI studies on face processing over the last years, often in the context of hemispheric lateralization (e.g., Frässle et al, 2016aFrässle et al, , 2016bFrässle et al, , 2016cHildesheim et al, 2020;Sahraei et al, 2021;Thome et al, 2021;Zimmermann et al, 2019). In these studies, it was often necessary to assess the fMRI activation patterns not only at the group level, but also at the individual level, e.g., in order to determine the spatial location of core system regions for further analyses.…”
Section: Interindividual Variabiliy Of Hemispheric Lateralizationmentioning
confidence: 99%
“…It has been proposed that face pareidolia requires a match between external visual input and internal face templates. Using fMRI, researchers found that when an illusory face was detected from pure noise images, it was associated with blood-oxygen-level-dependent (BOLD) imaging activity in the face-selective areas, including bilateral OFA and FFA (Liu et al, 2014; Zhang et al, 2008; but see Zimmermann, Stratil, Thome, Sommer, & Jansen, 2019). Further whole brain analysis revealed a distributed network extending from the ventral occipitotemporal cortex to the prefrontal cortex and sublobar regions, indicating the activation of the internal face templates and top-down modulation on the external input.…”
Section: Previous Findings Of Individual Differences In Face Pareidoliamentioning
confidence: 99%